2018
DOI: 10.1007/s12182-018-0262-x
|View full text |Cite
|
Sign up to set email alerts
|

Controls on the organic carbon content of the lower Cambrian black shale in the southeastern margin of Upper Yangtze

Abstract: Control of various factors, including mineral components, primary productivity and redox level, on the total organic carbon (TOC) in the lower Cambrian black shale from southeastern margin of Upper Yangtze (Taozichong, Longbizui and Yanbei areas) is discussed in detail in this article. Mineral components in the study strata are dominated by quartz and clay minerals. Quartz in the Niutitang Formation is mainly of biogenic origin, and the content is in positive correlation with TOC, while the content of clay min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 70 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…Generally, the marine shale has relatively high quartz content, which has positive linear relation with TOC, because the lower part of the water body is in a strong reducing environment [16,72]. However, quartz content in the present study showed no obvious correlation with TOC, which indicates the Dalong Formation shale in the western area of the Lower Yangtze Platform probably experienced multiperiod hydrothermal activities, resulting in the quartz being of hydrothermal origin [73][74][75].…”
Section: Relationships Between Toc and Clay Minerals And Quartzmentioning
confidence: 72%
“…Generally, the marine shale has relatively high quartz content, which has positive linear relation with TOC, because the lower part of the water body is in a strong reducing environment [16,72]. However, quartz content in the present study showed no obvious correlation with TOC, which indicates the Dalong Formation shale in the western area of the Lower Yangtze Platform probably experienced multiperiod hydrothermal activities, resulting in the quartz being of hydrothermal origin [73][74][75].…”
Section: Relationships Between Toc and Clay Minerals And Quartzmentioning
confidence: 72%
“…They remain stable during the diagenesis of siliceous rocks and can be used to trace the source and origin of silicon in siliceous rocks. ,, Most classification schemes for siliceous materials are based on microscopic characteristics or genesis. Zhang et al observed under a microscope that silica is divided into primary terrigenous detrital particles and cryptocrystalline aggregates or chalcedony formed by silicification. Zhao et al divided the silica into terrigenous detrital quartz and quartz formed during diagenesis (including quartz formed during the transformation of clay minerals and biogenic quartz) through scanning electron microscope cathodoluminescence (SEM-CL) combined with major element analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical index of alteration (CIA) is commonly utilized to analyze the paleoclimate (Wedepohl 1971;Nesbitt and Young 1982;McLennan 1993;Ross and Bustin 2009a, b); the ratio of content of SiO 2 and Al 2 O 3 (SiO 2 /Al 2 O 3 ), the ratio of content of MnO and TiO 2 (MnO/TiO 2 ) and the ratio of content of yttrium and holmium (Y/Ho) are used to indicate the amount of the detrital influx (Ryuichi et al 1982;Webb and Kamber 2000); the ratio of content of vanadium and (vanadium plus nickel) (V/(V + Ni)), the ratio of content of vanadium and chromium (V/Cr), the ratio of content of nickel and cobalt (Ni/Co), EF Mo , EF U , EF V , EF Ni , the ratio of content of uranium and thorium (U/Th) and the ratio of content of cuprum and zincum (Cu/Zn) could indicate the redox environment of water (Algeo and Maynard 2004;Ross and Bustin 2009b;Pi et al 2014;Zhu et al 2018), and the ratio of content of phosphorus and titanium (P/Ti) and ratio of content of barium and aluminum (Ba/Al) could present the paleoproductivity (Dean et al 1997;Algeo et al 2011;Liu et al 2018). Currently, the accumulation characteristics of organic matter with the geochemical method for Niutitang Formation shale in China mainly focus in south of Yangtze platform (Liu et al 2015(Liu et al , 2016Xia et al 2015;Wu et al 2017;Zhou et al 2017Zhou et al , 2019Li et al , 2019Zhang et al 2018;Ma et al 2019;Awan et al 2020). The lithofacies of Niutitang Formation shale in South China could be divided into five types, including organic matter-rich siliceous shale, silty-siliceous shale, argillaceous shale, calcareous shale and silty-siliceous mixed shale (Yang et al 2016;Wu et al 2017).…”
Section: Introductionmentioning
confidence: 99%